2018
DOI: 10.3390/healthcare6040133
|View full text |Cite
|
Sign up to set email alerts
|

Factors Underlying Racial Disparities in Sepsis Management

Abstract: Sepsis, a syndrome characterized by systemic inflammation during infection, continues to be one of the most common causes of patient mortality in hospitals across the United States. While standardized treatment protocols have been implemented, a wide variability in clinical outcomes persists across racial groups. Specifically, black and Hispanic populations are frequently associated with higher rates of morbidity and mortality in sepsis compared to the white population. While this is often attributed to system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 80 publications
1
39
0
Order By: Relevance
“…Other notable factors in the current study associated with increased risk of AKI were longer ICU LOS and identifying as black as compared to white, both of which are risk factors supported by previous research (34)(35)(36). The association between IV vitamin C and AKI is not unique to this study; a study by Litwak et al observed a 12% increase in AKI in patients that received IV vitamin C but this did not reach statistical signi cance, likely due to small sample size (22).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Other notable factors in the current study associated with increased risk of AKI were longer ICU LOS and identifying as black as compared to white, both of which are risk factors supported by previous research (34)(35)(36). The association between IV vitamin C and AKI is not unique to this study; a study by Litwak et al observed a 12% increase in AKI in patients that received IV vitamin C but this did not reach statistical signi cance, likely due to small sample size (22).…”
Section: Discussionsupporting
confidence: 80%
“…Sub-analyses of the ICU sample revealed that age, longer ICU LOS, and receiving IV vitamin C remained predictors of AKI, while identifying as black and being male were no longer signi cant predictors. Older age, and ICU LOS are both known risk factors supported by previous research (34)(35)(36). A second subanalysis revealed that age and AKI remained signi cant predictors of in-hospital mortality, however high dose IV vitamin C use was no longer a statistically signi cant predictor of mortality once the sample was limited to ICU patients only.…”
Section: Discussionmentioning
confidence: 58%
“…114 Black and Latinx patients are more likely to be discharged home, with black patients less likely than white patients to see improvements in their daily life after critical illness. [115][116][117] Black and Latinx patients who are discharged to a skilled nursing facility often go to facilities with higher readmission rates and lower rates of successful discharge into the community. 118 To minimize the risk of CKD after COVID-19-related AKI, it is critical to ensure patients have access to post-acute care and nephrology care when clinically indicated.…”
Section: Racial and Ethnic Disparities And The Risk Of Ckd After Covid-19mentioning
confidence: 99%
“…Racial and ethnic disparities in health are common in the United States, apparent as both striking differences in the prevalence ( 1 ) as well as outcomes ( 2 ) of disease. Such disparities exist in every aspect of care, from diagnosis to management ( 3 ), particularly with regard to Black and Hispanic patients compared with White patients ( 4 ). The underpinnings of these differences are complex, relating to factors such as access to care, implicit or explicit biases from healthcare workers and systems, and social determinants of health ( 5 ).…”
mentioning
confidence: 99%